MARTIAN PERCHED CRATERS AND LARGE EJECTA VOLUME: EVIDENCE FOR EPISODES OF DEFLATION IN THE NORTHERN LOWLANDS - Meresse S.; Costard F.; Mangold N.; Baratoux D.; Boyce J.M. (My University, 2006)
The northern lowland plains, such as those found in Acidalia and Utopia Planitia, have high percentages of impact craters with fluidized ejecta. In both regions, the analysis of crater geometry from Mars Orbiter Laser Altimeter (MOLA) data has revealed large ejecta volumes, some exceeding the volume of excavation. Moreover, some of the crater cavities and fluidized ejecta blankets of these craters are topographically perched above the surrounding plains. These perched craters are concentrated between 40 and 70°N in the northern plains. The atypical high volumes of the ejecta and the perched craters suggest that the northern lowlands have experienced one or more episodes of resurfacing that involved deposition and erosion. The removal of material, most likely caused by the sublimation of ice in the materials and their subsequent erosion and transport by the wind, is more rapid on the plains than on the ejecta blankets. The thermal inertia difference between the ejecta and the surrounding plains suggests that ejecta, characterized by a lower thermal inertia, protect the underneath terrain from sublimation. This results in a decreased elevation of the plains relative to the ejecta blankets. Sublimation and eolian erosion can be particularly high during periods of high obliquity. © The Meteoritical Society, 2006.